The Use of Experiential Learning-Based Group Counseling Model to Improve Students’ Emotional Maturity - Siswanto, Joko; Sutoyo, Anwar; Japar, Muhammad (Jurnal Bimbingan Konseling, 2018)
The aim of this study was to enhance students’ emotional maturity through experiential learning group counseling service. The experiment research method of pre-test post-test control group design was used with involving 16 students as experimental group (N = 8) and control (N = 8). The result of data analysis by using Wilcoxon test and Mann-Whitney test showed that group counseling based on experiential learning was effective to improve students’ emotional maturity. Discussion of the results of this research is directed to identify the implications of the application of group counseling based on experiential learning in improving students’ emotional maturity.